STUDY ON LIFE QUALITY OF PATIENTS DIAGNOSED WITH HEAD AND NECK CANCER - Vlad Ioan Covrig; Victor Vlad Costan; Nicolae Sorin Axinte; Corina Elena Covrig; Adrian Constantin Vasilcovici; Cristian Constantin Budacu; Beatrice Gabriela Ioan (Romanian Society of Oral Rehabilitation, 2023)
Aim of study. The aim of study was the assessment of the life quality in relation to socio-demographic and individual parameters of patients diagnosed with head and neck neoplasms. Materials and Methods. A prospective, quantitative study was conducted on a sample of 62 patients diagnosed with malignant tumors of the head and neck, hospitalized and diagnosed in the Oral and Maxillofacial Surgery Clinic of the "Sf. Spiridon" Emergency County Hospital in Iași (n=30), and in the Oral and Maxillofacial Surgery Department of the Suceava County Hospital (n=32). Data collection was performed using two questionnaires: the BIQoL questionnaire, which assesses the quality of life based on self-image, and the EORTC QLQ-H&N35 questionnaire, which evaluates parameters directly associated with the quality of life of individuals with head and neck neoplasms. Data analysis was performed using Microsoft Excel and SPSS 29.0 software. Results. From the analysis of data collected using the BIQoL questionnaire, higher scores were recorded in the case of women, urban patients, patients with higher education levels, patients without comorbidities, and patients with intraoral lesion localization. The results obtained based on the EORTC QLQ-H&N35 questionnaire show low or moderate levels of impairment in the quality of life for most of the investigated items, with moderate degree of impairment for "social contacts" and "sexual activity". Conclusions. Patients with head and neck cancer face various forms of disfigurement, neurological disorders, sensory disturbances, and psychological disorders, as highlighted by BIQoL questionnaire and the EORTC QLQ-H&N35 questionnaire. The study results can be used in the development of a standardized tool for pre- and postoperative information and counseling for this category of patients and to understand the aspects that most significantly influence the quality of life of patients. These findings can guide oncologic surgeons in the approach of therapeutic decisions.